Photocatalytic transformation fate and toxicity of ciprofloxacin related to dissociation species: Experimental and theoretical evidences - Si Li; Taobo Huang; Du, Penghui; Liu, Wen; Jiangyong Hu (Water Research, 2020)
Chemical speciation of ionizable antibiotics greatly affects its photochemical kinetics and mechanisms; however, the mechanistic impact of chemical speciation is not well understood. For the first time, the impact of different dissociation species (cationic, zwitterionic and anionic forms) of ciprofloxacin (CIP) on its photocatalytic transformation fate was systematically studied in a UVA/LED/TiO2 system. The dissociation forms of CIP at different pH affected the photocatalytic degradation kinetics, transformation products (TPs) formation as well as degradation pathways. Zwitterionic form of CIP exhibited the highest degradation rate constant (0.2217 ± 0.0179 min−1), removal efficiency of total organic carbon (TOC) and release of fluoride ion (F−). Time-dependent evolution profiles on TPs revealed that the cationic and anionic forms of CIP mainly underwent piperazine ring dealkylation, while zwitterionic CIP primarily proceeded through defluorination and piperazine ring oxidation. Moreover, density functional theory (DFT) calculation based on Fukui index well interpreted the active sites of different CIP species. Potential energy surface (PES) analysis further elucidated the reaction transition state (TS) evolution and energy barrier (ΔEb) for CIP with different dissociation species after radical attack. This study provides deep insights into degradation mechanisms of emerging organic contaminants in advanced oxidation processes associated to their chemical speciation.
Keywords: Ciprofloxacin; Density functional theory; Dissociation species; Photocatalysis; Transformation intermediates